Effectiveness of Team-Based Learning-Inquiry Learning Tools on Online Learning - Mustapa, Darmansya A; Arbie, Asri; Buhungo, Trisnawaty Junus; Nuayi, Abd. Wahidin (Jurnal Pendidikan Fisika, 2022)
The learning process carried out online today is still less effective, which makes it difficult for students to understand the material and concepts being taught. The purpose of this study was to find out how effective the use of team-based learning-inquiry devices is in online learning with WhatsApp assisted and zoom meetings. The research was conducted at SMAN 1 Telaga Biru, and class X MIPA3 was selected as the research sample using simple random sampling. The results showed that the average percentage of student activity for four meetings after being implemented in team-based learning-inquiry tools reached 86.60%, with high criteria. In addition, there was an increase in student learning outcomes in the cognitive domain individually at the first and second meetings with an N-gain score of 0.71 and for the third and fourth meetings with an N-gain score of 0.74. In the cognitive domain as a group, at the first and second meetings, they achieved an N-gain score of 0.95, and at the third and fourth meetings, they obtained an N-gain of 1. The average student learning outcomes for the affective and psychomotor domains during the four meetings reached 86.60% and 86.61%, with a high category. This study concludes that the physics learning device developed with the team-based learning model is effective in increasing students' activities and learning outcomes in physics.